Relative efficacy of natural resource use in Gobhi Sarson (Brassica napus) in Himachal Pradesh, India (Journal of Oilseed Brassica, 2026)
An experiment was conducted during Rabi 2010-11 to 2014-15 with an objective to quantify natural resource use by gobhi sarson in terms of heat use efficiency, radiation use efficiency and water use efficiency to facilitate the identification of varieties suitable for different sowing environments. In all the five varieties of gobhi sarson viz., GSL-1, ONK-1, HPN- 1, HPN-3 and Hyola-401 (hybrid) sown on 20th Oct, 30th Oct and 10th Nov, it was observed that the days taken for completion of different phenological stages and their thermal units requirements from 90% siliquae filling to physiological maturity decreased with successive delay in sowing. The efficiency to use these resources vis-a-vis seed yield also decreased with delay in sowing.Water use efficiency was observed to be higher (3.0 to 5.3 kg/ha/mm) as compared to heat use efficiency (0.8 to 1.3 kg/ha/degreeday) and radiation use efficiency (0.5 to 0.8 kg/ha/MJ).The seed yield deceased with delay in sowing from 20th October (2.43 to 1.71 t/ha) to 10th November (1.79 to1.32 t/ha). The variety ONK- 1, when sown on 20th and 30th October was found to be more efficient in respect of heat use (1.5 kg/ha/degree day) and water use (5.3 kg/ha/mm) as compared to other varieties studied.